Anterior Cervical Discectomy and Fusion Outcomes in Patients With and Without Bariatric Surgery—Weight Loss Does Make a Difference. Issue 6 (15th March 2023) - Joo, Peter Y.; Zhu, Justin R.; Wilhelm, Christopher; Tang, Kevin; Day, Wesley; Moran, Jay; Grauer, Jonathan N.
Abstract : Study Design: A retrospective comparative cohort study. Objective: To compare outcomes of elective non-obese anterior cervical discectomy and fusion (ACDF) patients with those that underwent bariatric surgery (BS). Summary of Background Data: Morbid obesity (MO) has been associated with an increased risk of complications following procedures such as elective ACDF. While pre-emptive BS has been considered for those with MO (body mass index [BMI] ≥35 kg/m 2 ), the impact of this intervention on BMI and its resultant correlation with surgical outcomes remains limited. Methods: The PearlDiver 2010-Q1 2020 MSpine database was used to identify patients undergoing elective isolated ACDF. Three sub-cohorts were defined as follows: (1) Non-obese controls without a history of BS, (2) patients with BS procedure within two years with a BMI <35 kg/m 2 (BS+MO-), and (3) patients with BS procedure within the two years with a BMI ≥35 kg/m 2 (BS+MO+). Univariate and multivariate regression analyses were performed to compare 90-day adverse event rates adjusting for age, sex, Elixhauser Comorbidity Index, and length of stay. Kaplan-Meier analysis was performed to assess five-year cervical reoperation rates. Results: Of 160, 166 elective ACDF patients, prior BS was identified for 479. Of these, 136 patients were BS+MO- and 343 were BS+MO+. On multivariate analysis, BS+MO- were not at increased odds of adverse events, but BS+MO+ were at greater odds of 90-day pulmonary embolism (odds ratio 3.28, P =0.043), wound dehiscence (5.02, P <0.001), hematomas (2.52, P =0.042), and overall minor adverse events (1.61, P =0.011) compared with controls. Five-year reoperation rates were not significantly different between the groups. Conclusion: Twenty-eight percent of those with BS before ACDF fell out of the categorization of MO. Among this group, the odds of adverse events were similar to non-obese patients. These findings suggest that the psychological preparation and BS alone are insufficient to reduce the risk of adverse events after ACDF. Weight reduction must be achieved as well, ideally moving patients out of the BMI range for morbid obesity.